Inhibition of Thrombin-Neutralizing Activity of Antithrombin III by Steroid Hormones - Nagasawa, H; Kim, B K; Steiner, M; Baldini, M G (Thrombosis and Haemostasis, 1982)
Estrogens in high doses have been shown to inhibit, in vitro, the thrombin-neutralizing action of antithrombin III (AT III). In this study we investigate the effect of estrogens on AT III in greater detail. To increase the sensitivity of measurement of AT III activity in the absence of heparin, we have developed an assay system utilizing human platelets, AT III and thrombin. The two proteins derived from human plasma were prepared in high purity. Platelet aggregation was induced by approximately 0.02 NIH U of thrombin. AT III was added in amounts that suppressed 95% of the aggregation-inducing effect of thrombin. Estrogens blocked the thrombin-neutralizing effect of AT III in dose-dependent manner. This effect was shown to be specific for AT III. Neither aggregability of platelets nor aggregating effect of thrombin were affected by the steroid hormone. Evidence for binding of estrogen to AT III was obtained from changes in intrinsic fluorescence of AT III. Activity of AT III was also reduced in increasing order of effectiveness by cholesterol, cortisone, testosterone and progesterone. Our studies suggest a direct effect of estrogens and other steroids on AT III, altering its specific neutralization of thrombin.
Keywords: Antithrombin III; Estrogen; Platelet aggregation; Thrombin; Crossed immunoelectrophoresis